Hopelessness and loneliness among suicide attempters in school-based samples of Taiwanese, Philippine and Thai adolescents - Randy M. Page (2018)
The aim of this study was to assess the level of suicide attempts in three school-based samples of Southeast Asian adolescents (Taipei, Taiwan; the Philippines; Chiang Mai, Thailand) and determine whether adolescent suicide attempters score higher on measures of hopelessness and loneliness relative to nonattempters. It was hypothesized that hopelessness and loneliness would be related to suicide attempts, and that hopelessness would continue to be associated with suicide attempts when controlling for loneliness. The prevalence of suicide attempts across the three samples of Asian youth were not consistent with Taiwanese girls and boys as the most likely to have ever attempted suicide. As expected, results showed that suicide attempters (in past 12 months and ever) scored higher on hopelessness and loneliness than nonattempters across all three samples and for both genders. However, the statistical control of loneliness demonstrably weakened the association between suicide attempt behaviour and hopelessness across the samples and for both genders, and resulted in nonsignificant ANCOVA tests for some of the sample-gender groups. These results attest to the need for more research investigating connections between youth suicide attempts, hopelessness and loneliness in adolescent populations. Loneliness should be included as a potential determinant of youth suicidal behaviour in future research. Copyright © 2006 SAGE Publications.